Management of severe open tibial fractures: the need for combined orthopaedic and plastic surgical treatment in specialist centres. - Naique, S; Pearse, M; Nanchahal, J (2006)
Although it is widely accepted that grade IIIB open tibial fractures require combined specialised orthopaedic and plastic surgery, the majority of patients in the UK initially present to local hospitals without access to specialised trauma facilities. The aim of this study was to compare the outcome of patients presenting directly to a specialist centre (primary group) with that of patients initially managed at local centres (tertiary group). We reviewed 73 consecutive grade IIIB open tibial shaft fractures with a mean follow-up of 14 months (8 to 48). There were 26 fractures in the primary and 47 in the tertiary group. The initial skeletal fixation required revision in 22 (47%) of the tertiary patients. Although there was no statistically-significant relationship between flap timing and flap failure, all the failures (6 of 63; 9.5%) occurred in the tertiary group. The overall mean time to union of 28 weeks was not influenced by the type of skeletal fixation. Deep infection occurred in 8.5% of patients, but there were no persistently infected fractures. The infection rate was not increased in those patients debrided more than six hours after injury. The limb salvage rate was 93%. The mean limb functional score was 74% of that of the normal limb. At review, 67% of patients had returned to employment, with a further 10% considering a return after rehabilitation. The times to union, infection rates and Enneking limb reconstruction scores were not statistically different between the primary and tertiary groups. The increased complications and revision surgery encountered in the tertiary group suggest that severe open tibial fractures should be referred directly to specialist centres for simultaneous combined management by orthopaedic and plastic surgeons.